A SIMPLE EFFORT TO ENHANCE SOLUBILITY AND DISSOLUTION RATE OF SIMVASTATIN USING CO-CRYSTALLIZATION - Sopyan, Iyan; Fudholi, Achmad; Muchtaridi, Muchtaridi; Puspitasari, Ika (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The main objective of this study was to explore co-crystallization as an effort to enhance the solubility of simvastatin (SV) using tartaric acid (TA) as co-former. Methods: The simulation of molecular modeling of TA against SV has been done by in silico using auto dock 4.2. A preparation of co-crystal carried out by using solvent drops grinding (SGD) with an equimolar ratio. A co-crystal formed was confirmed by scanning electron microscopy (SEM), saturated solubility test, in vitro dissolution test, infrared spectrophotometry (FTIR), powder X-ray diffraction (PXRD), and differential scanning calorimetry (DSC). Results: The in silico studies showed that the interaction of TA and SV has synthon molecular by hydrogen bonding. An increasing of solubility and in vitro dissolution profile of co-crystal resulted as compared to the value of pure SV and its physical mixer. Characterizations of a co-crystal SV: TA (1: 1) including SEM, FTIR, PXRD, and DSC have indicated the formation of new solid crystal phase that different compared to SV, TA, and its physical mixture. Conclusion: The co-crystallization has been used to enhance the solubility and dissolution of simvastatin. All characterization either in silico and in vitro has shown the formation of co-crystal SV: TA (1:1).